New 1, 3, 4-Oxadiazole Based Photosensitizers for Dye Sensitized Solar Cells (DSSCs). (26th November 2015) - Mehmood, Umer; Hussein, Ibnelwaleed A.; Daud, Muhammad
Abstract : 1, 3, 4-Oxadiazole based photosensitizers with biphenyl, naphthalene, anthracene, and triphenylamine as the electron-donating moiety were synthesized for solar cell applications. In these photosensitizers, cyano groups were introduced as the electron acceptor and the anchor group because of their high electron-withdrawing ability and strong bonding to the semiconductor. Oxadiazole isomers were used as the π -conjugation system, which bridges the donor-acceptor systems. The electrochemical and optical properties of the sensitizers were investigated both in their native form and upon incorporation into dye sensitized solar cells. The results of UV-visible absorption spectroscopy, electrochemical impedance spectroscopic measurements, and photocurrent voltage characteristics indicate that 1, 3, 4-oxadiazole pi-spacer with the anthracene moiety has the highest efficiency of 2.58%. Density functional theory was employed to optimize the structures of the sensitizers and the TiO2 cluster.